Binding Proteins for an Ecdysone Metabolite in the Crustacean Hepatopancreas - Gorell, Thomas A. (1972)
When crustacean hepatopancreas is incubated in the presence of α-(3)H]ecdysone of high specific activity and is then homogenized and centrifuged, a peak of protein-radioactivity is recovered after gel filtration of the 105,000 × g supernatant. Analysis of this peak by sucrose gradient centrifugation revealed the presence of two complexes of protein and labeled material (∼11.5 S and 6.35 S). The same results were obtained in vivo. On standing at low ionic strength, the lighter component disappeared, suggesting that the heavier component is an aggregate of the lighter one. Chemical analysis of radioactive material in the complex revealed that it is not α- or β-ecdysone nor any previously described metabolite of the ecdysones. This new metabolite of α-ecdysone is found mainly in the incubated hepatopancreas. Partial structures consistent with the analytical data are inferred for this metabolite. It is suggested that the metabolite may be active in the action of molting hormone.